Hydrophobic self-skinning high-resilience polyurethane composite material as well as preparation method and application thereof

By designing a hydrophobic self-skinned high-resistance polyurethane combination material, using components A and components B of specific ratios, the problem of degradation of existing polyurethane materials in water environments is solved, and high hydrophobicity, moisture and heat resistance and excellent physical properties are achieved, and it is suitable for materials such as ship seats.

CN119875066AActive Publication Date: 2025-04-25SHANDONG INOV POLYURETHANE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510379231.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing polyurethane self-crusting materials are susceptible to erosion by factors such as ultraviolet rays, salt spray, and moisture under complex and changeable environmental conditions on water, resulting in reduced performance and poor surface phenomena.

Method used

The hydrophobic self-scaling high-resistance polyurethane combination material is used. The combination material is made of mixing component A and component B in a specific mass ratio. Component A includes polyether polyols, chain extenders, crosslinkers, etc. Component B includes castor oil polyols, MDI, etc. Through molecular structure design and optimization of the catalyst system, the hydrophobic properties and physical properties of the material are improved.

Benefits of technology

It significantly improves the hydrophobic properties, moisture and heat resistance and physical properties of the material, and can maintain stability and performance in complex water environments and extend service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of polyurethane, and particularly relates to a hydrophobic self-skinning high-resilience polyurethane composite material as well as a preparation method and application thereof. The polyurethane composite material is prepared from a component A and a component B according to the mass ratio of 100: (45-65), and the component A comprises the following raw materials: polyether polyol 1, polyether polyol 2, polymer polyol, a chain extender, a cross-linking agent, a foaming agent, a foam stabilizer, a composite catalyst, an antioxidant and an ultraviolet light absorber; the component B comprises the following raw materials: castor oil polyol, polyether polyol 3, pure MDI, liquefied MDI and polymerized MDI; the prepared polyurethane composite material has excellent physical properties, moisture and heat resistance and hydrophobicity, and a steamship seat material prepared from the polyurethane composite material can effectively cope with complex and changeable environmental conditions on water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane, and in particular relates to a hydrophobic self-skinning high-resilience polyurethane composite material and a preparation method and application thereof. Background Art

[0002] Modern seafarers and passengers have increasing requirements for the safety and comfort of ship facilities. At the same time, due to the complex and changeable sailing environment of ships, their seats are exposed to harsh conditions such as direct sunlight, wind and rain, and salt spray corrosion for a long time. The material of ship seats must have excellent weather resistance and not be easily aged, faded, deformed or damaged due to ultraviolet radiation, high temperature and high humidity environment, and salt spray corrosion, ensuring that the performance can be maintained during long-term use. In addition, the seats must have sufficient strength to withstand the impact force caused by wind and waves and turbulence during the voyage of the ship, as well as the force in emergencies (such as collisions), while ensuring that the seats will not be damaged when they are under pressure of a certain multiple of the weight of passengers.

[0003] Polyurethane self-skinning materials have high strength, toughness and wear resistance, and can withstand the bumps and vibrations during the ship's journey and the frequent use of passengers, and are not prone to cracking, deformation and other problems. However, under the complex and changeable environmental conditions on the water, conventional polyurethane self-skinning materials will be corroded by ultraviolet rays, salt spray, humidity and other factors, resulting in performance degradation, and the surface may have undesirable phenomena such as discoloration and powdering.

[0004] Therefore, it is particularly necessary to develop a new polyurethane self-skinning material to meet the current stringent requirements for high hydrophobicity, moisture and heat resistance, and high physical properties. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a hydrophobic self-skinning high-resilient polyurethane composite material, which has excellent physical properties, moisture and heat resistance, and hydrophobic properties. The ship seat material prepared using the composite material can effectively cope with the complex and changeable environmental conditions on the water.

[0006] Another object of the present invention is to provide a preparation method and application of a hydrophobic self-skinning high-resilience polyurethane composite material.

[0007] The technical solution adopted by the present invention is as follows: The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:(45-65), wherein component A includes the following raw materials in parts by mass: Polyether polyol 1: 40-60 parts; Polyether polyol 2: 10-20 parts; Polymer polyol: 30-50 parts; Chain extender: 5-10 parts; Cross-linking agent: 0.4-1.2 parts; Foaming agent: 0.8-1.2 parts; Foam stabilizer: 0.5-1.0 parts; Composite catalyst: 1-1.2 parts; Antioxidant: 0.5-1 part; Ultraviolet absorber: 0.5-1 part; Component B includes the following raw materials in parts by weight: Castor oil polyol: 4-7 parts; Polyether polyol 3: 2-5 parts; Pure MDI: 20-30 parts; Liquefied MDI: 60-80 parts; Polymeric MDI: 5-10 parts; The functionality of the polyether polyol 1 is 3, and the hydroxyl value is 21-24 mgKOH / g; preferably, it is CHE-822P produced by Changhua Chemical Technology Co., Ltd.

[0008] The functionality of the polyether polyol 2 is 2, and the hydroxyl value is 26.5-57.5 mgKOH / g; preferably, it is one of INOVOL C220, INOVOL C230 or INOVOL C240A produced by Shandong Yinuowei New Materials Co., Ltd.

[0009] The functionality of the polyether polyol 3 is 3, and the hydroxyl value is 440-460 mgKOH / g; preferably, INOVOL C304 produced by Shandong INOVOL New Materials Co., Ltd. The castor oil polyol is prepared by carrying out a hydrosilylation reaction between castor oil and decamethyldihydrogenpentasiloxane.

[0010] The functionality of the polymer polyol is 3, the hydroxyl value is 22.0-27.0 mgKOH / g, and the solid content is 26.0-30.0%; preferably, CHP-H30 produced by Changhua Chemical Technology Co., Ltd.

[0011] The chain extender is one or more of ethylene glycol and 1,4-butanediol; the cross-linking agent is one or more of diethanolamine and triethanolamine.

[0012] The foaming agent is water.

[0013] The foam stabilizer is an organosilicon foam stabilizer, preferably UA-8823LV produced by Hemu New Materials Technology (Shanghai) Co., Ltd.

[0014] The composite catalyst is a mixture of a delayed catalyst, a foaming catalyst and an auxiliary catalyst, wherein the delayed catalyst is preferably XR Cat 8154, the foaming catalyst is preferably XR Cat 617, and the auxiliary catalyst is preferably XR Cat3040, all of which are purchased from Shanghai Xinrui New Material Technology Co., Ltd.

[0015] The antioxidant is RIANOX ® 1135, purchased from Tianjin Lianlong New Materials Co., Ltd.

[0016] The ultraviolet absorber is RIASORB ® UV-1130 was purchased from Tianjin Lianlong New Materials Co., Ltd.

[0017] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of (1.2-1.5):1 are mixed, and reacted at 95-105°C for 7.5-8.5h under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used is 0.8-1wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0018] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: polyether polyol 1, polyether polyol 2, polymer polyol, chain extender, crosslinking agent, foaming agent, foam stabilizer, composite catalyst, antioxidant and ultraviolet absorber are put into a reactor, the temperature is raised to 40-50°C, and the materials in the reactor are stirred at a stirring speed of 30-40 r / min for 40-50 min. After the stirring is completed, component A is obtained; (2) Preparation of component B: Castor oil polyol, polyether polyol 3, pure MDI, liquefied MDI and polymerized MDI are mixed, heated to 80-85° C., and the materials in the reactor are stirred at a stirring speed of 30-40 r / min for 40-50 min. After the stirring is completed, component B is obtained; (3) After mixing component A and component B evenly according to the mass ratio, inject them into the mold, open the mold and mature them after 4-5 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0019] The hydrophobic self-skinning high-resilience polyurethane composite material is used for ship seat materials.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a composite catalyst composed of a delayed catalyst, a foaming catalyst and an auxiliary catalyst to ensure that the material has sufficient fluidity during the preparation process, which is not only conducive to the uniform reaction, but also significantly improves the production efficiency. At the same time, the composite catalyst system can effectively promote the maturation process of the product skin, so that the final hydrophobic self-skinning high-resilience polyurethane composite material has a denser skin structure, thereby enhancing the durability and service life of the product; (2) The present invention introduces a castor oil hydrophobic group containing a silane structure and a small molecule polyether structure through molecular structure design, which not only significantly improves the hydrophobicity of the product, enabling it to maintain long-term stability in a humid environment, but also gives the product excellent physical properties, such as high strength, high resilience and good aging resistance. These performance improvements make the polyurethane composite material of the present invention particularly suitable for preparing materials such as ship seats; (3) The preparation method of the present invention can stably produce products with excellent performance by precisely controlling the ratio of component A and component B and the preparation conditions. The operation is simple and easy to industrialize. DETAILED DESCRIPTION

[0021] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0022] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.

[0023] Some of the raw materials used in the examples and comparative examples are described as follows: CHE-822P, CHP-H30: purchased from Changhua Chemical Technology Co., Ltd.; INOVOL C220, INOVOL C230, INOVOL C240A, INOVOL C304: purchased from Shandong Yinuowei New Materials Co., Ltd.; RIASORB ® UV-1130、RIANOX ® 1135: purchased from Tianjin Lianlong New Materials Co., Ltd.; XR Cat 8154, XR Cat 617, XR Cat 3040: purchased from Shanghai Xinrui New Material Technology Co., Ltd.; UA-8823LV: purchased from Hemu New Materials Technology (Shanghai) Co., Ltd.; DXCAT ® A-1, DXCAT ® A33: Purchased from Shandong Dingxin New Material Technology Co., Ltd.

[0024] Example 1 The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:45, wherein component A includes the following raw materials in parts by mass: CHE-822P: 60 copies; INOVOL C220: 10 parts; CHP-H30: 30 parts; Ethylene glycol: 5 parts; Diethanolamine: 0.4 parts; UA-8823LV: 0.5 parts; XR Cat 617: 0.2 parts; XR Cat 8154: 0.4 copies; XR Cat 3040: 0.4 parts; Water: 0.8 parts; RIASORB ® UV-1130: 0.5 parts; RIANOX ® 1135: 0.5 parts; Component B includes the following raw materials in parts by weight: Castor oil polyol: 4 parts; INOVOL C304: 5 parts; Pure MDI: 20 parts; Liquefied MDI: 80 parts; Polymeric MDI: 5 parts.

[0025] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of 1.2:1 were mixed, and reacted at 95°C for 7.5h under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used was 0.8wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0026] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: CHE-822P, INOVOL C220, CHP-H30, ethylene glycol, diethanolamine, UA-8823LV, water, XR Cat 617, XR Cat 8154, XR Cat 3040, RIASORB ® UV-1130 and RIANOX ®1135 is put into the reactor, the temperature is raised to 40°C, the materials in the reactor are stirred at a stirring speed of 30r / min for 40min, and after the stirring is completed, component A is obtained; (2) Preparation of component B: Castor oil polyol, INOVOL C304, pure MDI, liquefied MDI and polymerized MDI were mixed, heated to 80°C, and stirred at a stirring speed of 30 r / min for 40 min. After the stirring was completed, component B was obtained, and its NCO content was 25.95±0.5%; (3) Component A and component B were mixed evenly in a mass ratio of 100:45, injected into a mold, and opened and matured after 4 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0027] Example 2 The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:55, wherein component A includes the following raw materials in parts by mass: CHE-822P: 50 copies; INOVOL C230: 10 parts; CHP-H30: 40 parts; 1,4-Butanediol: 10 parts; Triethanolamine: 1.2 parts; UA-8823LV: 0.6 parts; XR Cat 617: 0.1 part; XR Cat 8154: 0.4 copies; XR Cat 3040: 0.6 parts; Water: 0.9 parts; RIASORB ® UV-1130: 0.7 parts; RIANOX ® 1135: 0.7 parts; Component B includes the following raw materials in parts by weight: Castor oil polyol: 5 parts; INOVOL C304: 4 parts; Pure MDI: 30 parts; Liquefied MDI: 60 parts; Polymeric MDI: 10 parts.

[0028] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of 1.3:1 were mixed, and reacted at 100°C for 8 hours under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used was 0.9wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0029] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: CHE-822P, INOVOL C230, CHP-H30, 1,4-butanediol, triethanolamine, UA-8823LV, water, XR Cat 617, XR Cat 8154, XR Cat 3040, RIASORB ® UV-1130 and RIANOX ® 1135 was put into the reactor, the temperature was raised to 45°C, and the materials in the reactor were stirred at a stirring speed of 35r / min for 45min. After the stirring was completed, component A was obtained; (2) Preparation of component B: Castor oil polyol, INOVOL C304, pure MDI, liquefied MDI and polymerized MDI were mixed and heated to 82°C. The materials in the reactor were stirred at a stirring speed of 35 r / min for 45 min. After the stirring was completed, component B was obtained, and its NCO content was 26.43±0.5%; (3) Component A and component B were mixed evenly in a mass ratio of 100:55, injected into a mold, and opened and matured after 4.5 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0030] Example 3 The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:65, wherein component A includes the following raw materials in parts by mass: CHE-822P: 40 copies; INOVOL C240A: 10 parts; CHP-H30: 50 parts; Ethylene glycol: 6 parts; 1,4-Butanediol: 4 parts; Diethanolamine: 0.4 parts; Triethanolamine: 0.4 parts; UA-8823LV: 0.7 parts; XR Cat 617: 0.2 parts; XR Cat 8154: 0.5 parts; XR Cat 3040: 0.3 parts; Water: 1 part; RIASORB ® UV-1130: 0.8 parts; RIANOX ® 1135: 0.8 parts; Component B includes the following raw materials in parts by weight: Castor oil polyol: 6 parts; INOVOL C304: 3 parts; Pure MDI: 25 parts; Liquefied MDI: 70 parts; Polymeric MDI: 5 parts.

[0031] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of 1.4:1 were mixed, and reacted at 105°C for 8.5h under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used was 1wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0032] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: CHE-822P, INOVOL C240A, CHP-H30, ethylene glycol, 1,4-butanediol, diethanolamine, triethanolamine, UA-8823LV, water, XR Cat 617, XR Cat 8154, XR Cat 3040, RIASORB ® UV-1130 and RIANOX ® 1135 is put into the reactor, the temperature is raised to 50°C, the materials in the reactor are stirred at a stirring speed of 40r / min for 50min, and after the stirring is completed, component A is obtained; (2) Preparation of component B: Castor oil polyol, INOVOL C304, pure MDI, liquefied MDI and polymerized MDI were mixed, heated to 80°C, and stirred at a stirring speed of 35 r / min for 45 min. After the stirring was completed, component B was obtained, and its NCO content was 26.37±0.5%; (3) Component A and component B were mixed evenly in a mass ratio of 100:65, injected into a mold, and opened and matured after 5 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0033] Example 4 The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:60, wherein component A includes the following raw materials in parts by mass: CHE-822P: 50 copies; INOVOL C220: 20 parts; CHP-H30: 30 parts; Ethylene glycol: 4 parts; 1,4-Butanediol: 4 parts; Diethanolamine: 0.5 parts; Triethanolamine: 0.5 parts; UA-8823LV: 0.8 parts; XR Cat 617: 0.3 parts; XR Cat 8154: 0.4 copies; XR Cat 3040: 0.4 parts; Water: 1.1 parts; RIASORB ® UV-1130: 0.9 parts; RIANOX ® 1135: 0.9 parts; Component B includes the following raw materials in parts by weight: Castor oil polyol: 7 parts; INOVOL C304: 2 parts; Pure MDI: 30 parts; Liquefied MDI: 65 parts; Polymeric MDI: 7 parts.

[0034] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of 1.5:1 were mixed, and reacted at 100°C for 8 hours under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used was 0.8wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0035] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: CHE-822P, INOVOL C220, CHP-H30, ethylene glycol, 1,4-butanediol, diethanolamine, triethanolamine, UA-8823LV, water, XR Cat 617, XR Cat 8154, XR Cat 3040, RIASORB ® UV-1130 and RIANOX ®1135 is put into the reactor, the temperature is raised to 40°C, the materials in the reactor are stirred at a stirring speed of 30r / min for 40min, and after the stirring is completed, component A is obtained; (2) Preparation of component B: Castor oil polyol, INOVOL C304, pure MDI, liquefied MDI and polymerized MDI were mixed, heated to 80°C, and stirred at a stirring speed of 35 r / min for 45 min. After the stirring was completed, component B was obtained, and its NCO content was 26.84±0.5%; (3) Component A and component B were mixed evenly in a mass ratio of 100:60, injected into a mold, and opened and matured after 4 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0036] Example 5 The hydrophobic self-skinning high-resilience polyurethane composite material is made of component A and component B in a mass ratio of 100:58, wherein component A includes the following raw materials in parts by mass: CHE-822P: 40 copies; INOVOL C240A: 15 parts; CHP-H30: 45 parts; Ethylene glycol: 4 parts; 1,4-Butanediol: 2 parts; Diethanolamine: 0.6 parts; Triethanolamine: 0.6 parts; UA-8823LV: 1; XR Cat 617: 0.2 parts; XR Cat 8154: 0.4 copies; XR Cat 3040: 0.6 parts; Water: 1.2 parts; RIASORB ® UV-1130: 1 part; RIANOX ® 1135: 1 copy; Component B includes the following raw materials in parts by weight: Castor oil polyol: 4 parts; INOVOL C304: 4 parts; Pure MDI: 20 parts; Liquefied MDI: 75 parts; Polymeric MDI: 10 parts.

[0037] The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of 1.3:1 were mixed, and reacted at 95°C for 8 hours under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used was 0.9wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

[0038] The preparation method of the hydrophobic self-skinning high-resilience polyurethane composite material comprises the following steps: (1) Preparation of component A: CHE-822P, INOVOL C240A, CHP-H30, ethylene glycol, 1,4-butanediol, diethanolamine, triethanolamine, UA-8823LV, water, XR Cat 617, XR Cat 8154, XR Cat 3040, RIASORB ® UV-1130 and RIANOX ® 1135 was put into the reactor, the temperature was raised to 45°C, the materials in the reactor were stirred at a stirring speed of 40r / min for 45min, and after the stirring was completed, component A was obtained; (2) Preparation of component B: Castor oil polyol, INOVOL C304, pure MDI, liquefied MDI and polymerized MDI were mixed, heated to 85°C, and stirred at a stirring speed of 40 r / min for 50 min. After the stirring was completed, component B was obtained, and its NCO content was 26.53±0.5%; (3) Component A and component B were mixed evenly in a mass ratio of 100:58, injected into a mold, and opened and matured after 5 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

[0039] Comparative Example 1 The difference from Example 4 is that the INOVOL C220 in component A is replaced with the same mass fraction of CHE-822P, and the rest is the same as Example 4.

[0040] Comparative Example 2 The difference from Example 4 is that the composite catalyst in component A is replaced by 0.1 parts of DXCAT ® A-1 with 0.5 parts of DXCAT ® A33, the rest is the same as in Example 4.

[0041] Comparative Example 3 The difference from Example 4 is that RIASORB is not added to component A. ® UV-1130 and RIANOX ® 1135, and the rest is the same as in Example 4.

[0042] Comparative Example 4 The difference from Example 4 is that the castor oil polyol in component B is replaced with castor oil in the same mass portion, and the rest is the same as Example 4.

[0043] Comparative Example 5 The difference from Example 4 is that INOVOL C304 is not added to component B, and the rest is the same as Example 4.

[0044] The polyurethane composite materials prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests, and the test method was as follows: Density: Tested in accordance with GB / T 6343-2009; Surface hardness: Tested in accordance with GB / T 531-1999; Tensile strength: Tested in accordance with GB / T 6344-2008; Elongation at break: Tested in accordance with GB / T 6344-2008; Dimensional stability: Tested in accordance with GB / T 8811-2018; Salt water resistance: Add 2 drops of 3.5wt.% NaCl solution on the surface of a sample with a surface size of 20mm×20mm. After 15 minutes, observe the penetration.

[0045] Water absorption: Tested in accordance with GB / T 8810-2005; Compression set: Tested in accordance with GB / T 6669-2008; Hygrothermal aging: After placing the sample under test at 95°C and 95% humidity for 200 hours, the mechanical properties, dimensional stability and salt water resistance of the product are tested respectively. The ratio of the mechanical properties of the sample after hygrothermal aging to the initial mechanical properties is calculated to obtain the hygrothermal aging retention rate. Dry aging: After placing the sample at 150°C for 72 hours, test the mechanical properties, dimensional stability and salt water resistance of the product respectively, and calculate the ratio of the mechanical properties of the sample after dry aging to the initial mechanical properties, that is, the dry aging retention rate; Low temperature: Place the sample under test at -60℃ for 24 hours and then test the dimensional stability of the product; The test results are shown in Table 1-2: Table 1 Performance test results of the embodiment

[0046] It can be seen from the data in Table 1 that the polyurethane composite materials prepared in Examples 1-5 have high hydrophobicity and excellent resistance to dry and wet heat aging, and also have good dry aging, wet heat aging and low temperature dimensional stability; wherein, the dry aging and wet heat aging retention rates of tensile strength are both higher than 85%, and the dry aging and wet heat aging retention rates of elongation at break are both greater than 80%.

[0047] Table 2 Comparative performance test results

[0048] From the comparison between Example 4 and Comparative Example 1, it can be seen that the addition of polyether diol in component A of the present invention can significantly improve the physical properties of the polyurethane composite material, thereby enabling it to withstand the impact force generated during navigation.

[0049] From the comparison between Example 4 and Comparative Example 2, it can be seen that the composite catalyst composed of the delayed catalyst, foaming catalyst and auxiliary catalyst used in component A of the present invention can ensure that the material has sufficient fluidity and that the product has a good appearance and excellent performance.

[0050] From the comparison between Example 4 and Comparative Example 3, it can be seen that the antioxidant and ultraviolet absorber added to the component A of the present invention can significantly improve the aging performance of the polyurethane combination material, thereby making it adaptable to complex navigation environments.

[0051] From the comparison between Example 4 and Comparative Examples 4 and 5, it can be seen that the highly hydrophobic B component synthesized by the present invention can not only improve the physical properties of the product, but also enhance its resistance to wet heat aging.

[0052] In general, the polyurethane composite material prepared by the present invention exhibits good high temperature aging resistance, wet heat aging resistance and excellent hydrophobic performance. The ship seat material made of the composite material can cope with various changes in the water environment and effectively extend the service life of the ship seat.

Claims

1. A hydrophobic self-skinning high-resilience polyurethane composite material, characterized in that: It is made of component A and component B in a mass ratio of 100: (45-65), wherein component A includes the following raw materials in mass fractions: Polyether polyol 1: 40-60 parts; Polyether polyol 2: 10-20 parts; Polymer polyol: 30-50 parts; Chain extender: 5-10 parts; Cross-linking agent: 0.4-1.2 parts; Foaming agent: 0.8-1.2 parts; Foam stabilizer: 0.5-1.0 parts; Composite catalyst: 1-1.2 parts; Antioxidant: 0.5-1 part; Ultraviolet absorber: 0.5-1 part; Component B includes the following raw materials in parts by weight: Castor oil polyol: 4-7 parts; Polyether polyol 3: 2-5 parts; Pure MDI: 20-30 parts; Liquefied MDI: 60-80 parts; Polymeric MDI: 5-10 parts; The functionality of the polyether polyol 1 is 3, and the hydroxyl value is 21-24 mgKOH / g; The functionality of the polyether polyol 2 is 2, and the hydroxyl value is 26.5-57.5 mgKOH / g; The functionality of the polyether polyol 3 is 3, and the hydroxyl value is 440-460 mgKOH / g; The castor oil polyol is prepared by carrying out a hydrosilylation reaction between castor oil and decamethyldihydrogenpentasiloxane.

2. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The functionality of the polymer polyol is 3, the hydroxyl value is 22.0-27.0 mgKOH / g, and the solid content is 26.0-30.0%.

3. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The chain extender is one or more of ethylene glycol and 1,4-butanediol; the cross-linking agent is one or more of diethanolamine and triethanolamine.

4. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The foaming agent is water; the foam stabilizer is an organic silicon foam stabilizer.

5. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The composite catalyst is a mixture of a delayed catalyst, a foaming catalyst and an auxiliary catalyst.

6. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The antioxidant is RIANOX ® 1135.

7. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The ultraviolet absorber is RIASORB ® UV-1130.

8. The hydrophobic self-skinning high-resilience polyurethane composite material according to claim 1, characterized in that: The preparation method of castor oil polyol comprises the following steps: In a nitrogen atmosphere, decamethyldihydrogen pentasiloxane and castor oil in a mass ratio of (1.2-1.5):1 are mixed, and reacted at 95-105°C for 7.5-8.5h under the action of chloroplatinic acid catalyst to obtain castor oil polyol, wherein the amount of chloroplatinic acid catalyst used is 0.8-1wt.% of the total mass of decamethyldihydrogen pentasiloxane and castor oil.

9. A method for preparing the hydrophobic self-skinning high-resilience polyurethane composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Preparation of component A: polyether polyol 1, polyether polyol 2, polymer polyol, chain extender, crosslinking agent, foaming agent, foam stabilizer, composite catalyst, antioxidant and ultraviolet absorber are put into a reactor, the temperature is raised to 40-50°C, and the materials in the reactor are stirred at a stirring speed of 30-40 r / min for 40-50 min. After the stirring is completed, component A is obtained; (2) Preparation of component B: Castor oil polyol, polyether polyol 3, pure MDI, liquefied MDI and polymerized MDI are mixed, heated to 80-85° C., and the materials in the reactor are stirred at a stirring speed of 30-40 r / min for 40-50 min. After the stirring is completed, component B is obtained; (3) After mixing component A and component B evenly according to the mass ratio, inject them into the mold, open the mold and mature them after 4-5 minutes to obtain a hydrophobic self-skinning high-resilient polyurethane composite material.

10. An application of the hydrophobic self-skinning high-resilience polyurethane composite material according to any one of claims 1 to 8, characterized in that: Used as ship seat material.

Citation Information

Patent Citations

  • Method for preparing castor oil-based polysiloxane polyol

    CN101775141A

  • Organic silicon modified polyurethane material and preparation method thereof

    CN114057973A

  • Hydrophobic high-strength soft polyurethane foam as well as preparation method and application thereof

    CN119350591A

  • Improved adhesion of silicone elastomer to polyurethane

    EP0262969A2

  • Adhesion of silicone elastomer to polyurethane

    US4681808A